A comparative analysis of road and rail performance in freight transport: an example from Nigeria. Issue 1 (31st December 2022) - Daramola, Adebukola
ABSTRACT: The research examines the implication of Nigeria's lopsided land transport structure for performance and efficiency in the freight transport sector using the Lagos–Kano corridor as a case study. A comparative analysis of road and rail performance in freight transport using defined performance indicators shows that road transport performed better on all but two indicators, namely, freight ton-kilometres moved per vehicle hour travelled and throughput per unit of energy consumed. Other performance indicators such as absolute throughput of freight, freight ton-kilometres performed, speed, freight throughput per unit cost of operation and revenue per ton of freight moved favoured roads over rail. Clearly, rail comparative advantage relates to capacity, but freight shippers are looking for speed that shortens vehicle turnaround time. The lesson is that freight shippers will not explore modal comparative advantages (such as capacity and lower freight rates) except such advantages are complemented with competitiveness conferred by technology (especially speed).